2000
DOI: 10.1076/0271-3683(200001)2011-hft035
|View full text |Cite
|
Sign up to set email alerts
|

Binocular summation in the fovea and peripheral field of anisometropic amblyopes

Abstract: Results are discussed in terms of tolerance to interocular sensitivity differences in the periphery and selective losses in cortical cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…We found that the extent of ocular dominance bias varied with both field location and hemisphere, with the foveal sites and ipsilateral hemisphere generally showing the largest bias. This finding is consistent with human psychophysical data showing larger sensitivity losses in amblyopic fovea (Hess & Pointer, 1985, Pardhan & Whitaker, 2000, Sireteanu & Fronius, 1981, Thomas, 1978) and further suggests a specific weakness of the cortical representation of the temporal retina of the amblyopic eye.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the extent of ocular dominance bias varied with both field location and hemisphere, with the foveal sites and ipsilateral hemisphere generally showing the largest bias. This finding is consistent with human psychophysical data showing larger sensitivity losses in amblyopic fovea (Hess & Pointer, 1985, Pardhan & Whitaker, 2000, Sireteanu & Fronius, 1981, Thomas, 1978) and further suggests a specific weakness of the cortical representation of the temporal retina of the amblyopic eye.…”
Section: Discussionsupporting
confidence: 90%
“…11, 14, 15, 20, 21, 28 However, a growing body of evidence suggests that the visual system in amblyopes may retain structural binocularity, despite being functionally monocular due to suppression from the fellow eye. 4 For example, when visual acuity and contrast are balanced between the eyes by diminishing luminance for better eye, binocular summation improves to normal in strabismic amblyopes.…”
Section: Introductionmentioning
confidence: 99%
“…The most common risk factors for developing amblyopia are anisometropia (unequal refractive error in the two eyes), strabismus (misalignment of visual axes) and another form of deprivation (e.g., congenital cataract) early in life (Kiorpes and McKee, 1999 ; Roper-Hall, 2007 ). In the case of anisometropic amblyopia, peripheral retina is generally normal (Yu et al, 1998 ; Pardhan and Whitaker, 2000 ), and spatial vision deficits are the consequence of chronic blur in the area of central retina during sensitive period for development of visual acuity (see Daw, 1998 ). Anisometropia becomes clinically significant when its magnitude reaches approximately 1 D in either one or both meridians (Benjamin, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Taking all into consideration, the central retina has a dominant effect on observed visual deficits in subjects with anisometropic amblyopia (Yu et al, 1998 ; Pardhan and Whitaker, 2000 ), thus we expect that the loss of physiological function of foveal vision in these individuals may affect specifically saccades in terms of their spatial and temporal properties during saccade delayed task.…”
Section: Introductionmentioning
confidence: 99%